1987
DOI: 10.1093/jn/117.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Balance and Clinical Observations in Young Men Fed a Manganese-Deficient Diet

Abstract: A balance study was conducted to determine the minimum requirement for manganese (Mn) and to examine the effects of Mn depletion. Seven male subjects, age 19-22, were fed a Mn-adequate diet of conventional foods (2.59 mg Mn/d, 135 mg cholesterol, and P:S ratio of 0.86) for 3 wk to establish base-line data. Then a purified diet containing 0.11 mg Mn/d was fed for 39 d (depletion), followed by two 5-d periods of 1.53 and 2.55 mg Mn/d (repletion). Diets, feces, urine, and integument were analyzed for Mn, and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(78 citation statements)
references
References 43 publications
0
75
0
3
Order By: Relevance
“…The SCF (1993) set an Acceptable Range of Intakes for adults at 1-10 mg/day, considering that most intakes were around 2-3 mg/day, that some reached 8.3 mg/day (Friedman et al, 1987;Hurley and Keen, 1987), that a basal average requirement of 0.74 mg/day had been derived from balance studies (Freeland-Graves et al, 1988) and that negative balances observed on dietary intakes between 1.21 and 2.89 mg/day could represent homeostasis (Freeland-Graves et al, 1988).…”
Section: Adultsmentioning
confidence: 99%
“…The SCF (1993) set an Acceptable Range of Intakes for adults at 1-10 mg/day, considering that most intakes were around 2-3 mg/day, that some reached 8.3 mg/day (Friedman et al, 1987;Hurley and Keen, 1987), that a basal average requirement of 0.74 mg/day had been derived from balance studies (Freeland-Graves et al, 1988) and that negative balances observed on dietary intakes between 1.21 and 2.89 mg/day could represent homeostasis (Freeland-Graves et al, 1988).…”
Section: Adultsmentioning
confidence: 99%
“…Le Manganèse est un élément essentiel dans la nutrition humaine et contribue à la formation de tissu conjonctif et dans le métabolisme des lipides et des carbohydrates (Atsdr.2000, Beliles RP, 1994. Le manganèse joue un rôle dans la minéralisation des os, dans le métabolisme des protéines, dans la régulation métabolique, dans le fonctionnement du système nerveux (Freelandgraves JH et al 1987, Hurley LS et Keen CL, 1987, Wedler FC, 1994, dans la protection cellulaire contre les radicaux libres et dans la formation des glycosaminoglycans (Wedler FC, 1994) et la synthèse du cholestérol (Freedlandgraves JH et al, 1987, Friedman BJ et al, 1987. Il joue aussi un rôle enzymatique important (Keen CL et al, 1990, Nrc, 1989.…”
Section: Introductionunclassified
“…Está diretamente envolvido com as enzimas fosfatase óssea, fosfatase alcalina e arginase, além de participar da síntese de proteínas que estimulam a ativação da DNA e da RNA polimerases (Wiberg e Neuman, 1957) e de colaborar com o metabolismo proteico e energético, e com síntese de colesterol e de mucopolissacarídeos (Friedman et al, 1987). Leach e Gross (1983) demonstraram que a deficiência de Mn na dieta de aves resultou em ovos com cascas mais finas, com alterações ultraestruturais na camada mamilar da casca e redução no teor de hexozamina e ácido hexurônico na matriz orgânica.…”
unclassified